2002
DOI: 10.1177/104973202129120331
|View full text |Cite
|
Sign up to set email alerts
|

Informal Networks among Women with HIV/AIDS: Present Support and Future Prospects

Abstract: Given the importance of informal support in the lives of chronically ill people, it is imperative to gain a deeper understanding of the nature and impact of HIV-positive women's informal networks. Through interviews with 37 women with HIV infection, the author explores women's social network composition and the extent to which these networks appear to facilitate or mediate the disruption caused by HIV/AIDS. Women reported having at least one person, usually a family member, on whom they could depend for emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 58 publications
0
28
0
4
Order By: Relevance
“…Similarly, those who perceived their social network as strong felt that emotional support and acceptance were clearly important, particularly in the initial stages of HIV infection, when stigma and perceived differences were critical issues than physical debilitation (Ciambrone 2002). According to Alula and Damen (2000) iddirs are also among the most important institutions for the successful implementation of the multisectoral responses to HIV pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, those who perceived their social network as strong felt that emotional support and acceptance were clearly important, particularly in the initial stages of HIV infection, when stigma and perceived differences were critical issues than physical debilitation (Ciambrone 2002). According to Alula and Damen (2000) iddirs are also among the most important institutions for the successful implementation of the multisectoral responses to HIV pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Women are more apt to seek out social support than their male counterparts are [10] and it is also undeniable that Ethiopian women have strong mutual help associations in which resources are pooled so as to cope up with their problems. These associations are sources of strength to the family at times of birth, disease, marriage and death [11].…”
Section: Introductionmentioning
confidence: 98%
“…One study found that women with HIV who used drugs were more likely to be rejected by lovers and families, apparently due to the stigma of drug use (Knowlton et al, 2011). As well, expectations about gender roles seem to lead men away from caregiving, and women's drug and substance abuse histories contributed to their small and/or unsupportive social networks (Ciambrone, 2002). Another study indicated that women living with HIV relied on children and friends for support more than men did (Smith & Rapkin, 1996).…”
Section: Caregiving and Social Supportmentioning
confidence: 96%
“…Moreover, a strong caregiving network has been found to help individuals adhere to a medication regime (Knowlton et al, 2011) and to reduce depressive symptoms (Simoni & Cooperman, 2000). Caregiving can play a key role in helping people gain a sense of meaning and control in their lives, as well as help with self-esteem issues (Ciambrone, 2002). Recent papers have stressed the need to link PLWH to services and engage them in the care system, along with continued support for risk reduction (Linsk, 2012).…”
Section: Caregiving and Social Supportmentioning
confidence: 98%